2021
DOI: 10.3329/bjsir.v56i1.52689
|View full text |Cite
|
Sign up to set email alerts
|

Chemometric model for rapid detection of urea and hydrogen peroxide in milk

Abstract: A simple and cost effective method has been developed for determination of adulteration in milk with urea and hydrogen peroxide by using chemometric modeling with Fourier Transform Infrared (FTIR) spectroscopic data. Milk samples were purchased from a dairy farm (South Banasree, Dhaka, Bangladesh) and spiked at different concentrations of urea and hydrogen peroxide. Spectral data of all samples were collected using ATR-FTIR spectrophotometer. After acquisition of spectral data, they were preprocessed with tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…The MLR scatterplot depicting all spectral ranges (Figure 4) indicates a good concordance between the reference values and the predicted FTIR values for urea bias, as evidenced by the R 2 , RMSEC, and MSE metrics. Our study's results compare favourably to those reported by Basak et al [52], who employed PLSR with a pre-processing technique known as multiplicative scatter correction (MSC) to quantify urea in milk, which achieved R 2 = 0.99, with an RMSE value of 3.35, which is higher than our study, which achieved below 1. They also found the presence of urea in six brands of commercial samples, as urea is naturally present in milk, but none of the samples contained higher than the permissible limit.…”
Section: Quantification Of Urea Adulteration In Uht Milk Regression A...supporting
confidence: 87%
See 1 more Smart Citation
“…The MLR scatterplot depicting all spectral ranges (Figure 4) indicates a good concordance between the reference values and the predicted FTIR values for urea bias, as evidenced by the R 2 , RMSEC, and MSE metrics. Our study's results compare favourably to those reported by Basak et al [52], who employed PLSR with a pre-processing technique known as multiplicative scatter correction (MSC) to quantify urea in milk, which achieved R 2 = 0.99, with an RMSE value of 3.35, which is higher than our study, which achieved below 1. They also found the presence of urea in six brands of commercial samples, as urea is naturally present in milk, but none of the samples contained higher than the permissible limit.…”
Section: Quantification Of Urea Adulteration In Uht Milk Regression A...supporting
confidence: 87%
“…Plus, the amide is a crucial protein group marker, and several types of amides with different protein samples may result in overlapping or weakening the transmittance values [25,51]. Therefore, it is necessary to use mathematical spectral transformations to extract meaningful information for qualitative and quantitative analyses [52]. The classification of the pure and adulterated UHT milk was further analysed by PCA and DA, and the quantification through the MLR model.…”
Section: Determination Of Significant Wavenumbers For Adulterated Uht...mentioning
confidence: 99%
“…Urea is not a natural component of milk, and it can cause digestive problems, kidney failure, and even death in many cases. Additionally, urea can react with other compounds in milk to form harmful chemicals such as formaldehyde, which is a known carcinogen [6]. Infrared spectroscopy (IR) and nuclear magnetic resonance (NMR) spectroscopy are powerful analytical techniques that can detect urea in milk based on its unique molecular properties.…”
Section: Ureamentioning
confidence: 99%
“…The purity of milk can be tested using various methods, such as the lactometer test, which measures the specific gravity of the milk, or the adulteration test, which detects the presence of common milk adulterants, like hydrogen peroxide. It is important and required to be aware of the potential health risks associated with consuming adulterated milk and to take appropriate measures to ensure that the milk you consume is safe and pure [6].…”
Section: Hydrogen Peroxidementioning
confidence: 99%
See 1 more Smart Citation